Macro-economic theory: a mathematical treatment - Allen, R. G. D. (London: Macmillan: New York, St. Martin's P., 1967)
This book on macro-economic theory is confined to a treatment of deterministics models in contrast to the stochastic model of econometric,and is largely limited to positive economics as opposed to the problems of planning and organisation
Bibliographical footnotes.
obn 23/01/2019
Loans
Keywords: Economics, Mathematical; Macroeconomics